Designing an Interoperable Health Information System for Enhanced Patient Record Accessibility - Murtadha Musallam Alsarhayd,; Mohammed Fahad Alnajim,; Ali Hussain Ali Almatrook,; Zinab Hassan Al Atia,; Huda Mubarak Alzahrani,; Haleemah Abdullah Alshokan,; Abdullah Hussain Alruwayshid,; Hawraa Sadiq Alzain,; Rawan Saleh Saleem,; Zainab Hajji Alkhulaif,; Fatimah Yassen Alomran,; Ghufran Abdualmohsen Aljumaiah,; et al. (International Journal of Medical Toxicology and Legal Medicine, 2024)
Healthcare systems often face challenges related to the secure and seamless sharing of patient records across institutions. Existing health information systems (HIS) are largely fragmented, lack interoperability, and fail to ensure robust data security. Conventional methods rely on centralized databases, which are vulnerable to breaches, data tampering, and unauthorized access, leading to inefficiencies in patient care and limited trust among stakeholders. This study proposes a novel interoperable health information system that leverages blockchain technology to address these limitations. Blockchain's decentralized, immutable ledger ensures secure and auditable sharing of patient data. The system also integrates FHIR/HL7 standards for interoperability, enabling consistent and standardized data exchange across diverse healthcare platforms. The proposed methodology involves a hybrid architecture comprising a blockchain network for storing transaction hashes, cloud storage for encrypted patient data, and a smart contract layer for automated access control and audit trails. Data flow is managed through an API middleware, connecting the blockchain and cloud systems with existing healthcare platforms. A user-friendly front-end interface is developed to enable doctors, patients, and administrators to access records securely. Preliminary results, demonstrate significant improvements. Data retrieval latency decreased by 45%, reflecting faster access to patient records. Data security, measured by immutable log integrity, improved by 85%, ensuring robust protection against breaches. Compliance with interoperability standards reached 92%, facilitating seamless data sharing. Additionally, patient trust and satisfaction scores increased by 40%, attributed to transparent access logs and secure record-sharing mechanisms. These outcomes highlight the scalability and security of the proposed framework, revolutionizing patient data management and enhancing healthcare delivery while building trust in digital health systems.